If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 3x = 14 + 7x Solving 2 + 3x = 14 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 2 + 3x + -7x = 14 + 7x + -7x Combine like terms: 3x + -7x = -4x 2 + -4x = 14 + 7x + -7x Combine like terms: 7x + -7x = 0 2 + -4x = 14 + 0 2 + -4x = 14 Add '-2' to each side of the equation. 2 + -2 + -4x = 14 + -2 Combine like terms: 2 + -2 = 0 0 + -4x = 14 + -2 -4x = 14 + -2 Combine like terms: 14 + -2 = 12 -4x = 12 Divide each side by '-4'. x = -3 Simplifying x = -3
| 2c-6=76 | | x+3x+3x+2=37 | | x+8+70+4x+2=180 | | 7=y-2 | | 9-19x-5-2x=7 | | x+8+70=4x+2 | | 12+ax=16 | | 1.5R=15 | | 6x-(5x+5)=-3 | | -25+4(2+5)=-61 | | 4x+2+70=x+8 | | 13x^2-104x+156=0 | | 9x+6x=36 | | 7x-6=22 | | 1-2c=-8 | | 6+12x+66+7x=180 | | 9x=6x+36 | | 6+12x+66+7x=90 | | 6+12x+66=7x | | 3f+6+9=13+5f | | 15x^2-180x+480=0 | | 8x=7x-1 | | a^6+7a^3+6=2 | | 6g+21=39 | | -2(2x-10)+29=3x | | a^2+10a=-21 | | -2(6-10n)=10(n-6) | | 8y=27 | | 5x-9=45 | | C(m)=0.4m+35 | | 17+t=43 | | 25-p=75 |